2018
DOI: 10.1029/2018gc007590
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Magmatic System Beneath the East Pacific Rise (8°20′ to 10°10′N): Implications for Tectonomagmatic Segmentation and Crustal Melt Transport at Fast‐Spreading Ridges

Abstract: Detailed images of the midcrustal magmatic system beneath the East Pacific Rise (8°20′–10°10′N) are obtained from 2‐D and 3‐D‐swath processing of along axis seismic data and are used to characterize properties of the axial crust, cross‐axis variations, and relationships with structural segmentation of the axial zone. Axial magma lens (AML) reflections are imaged beneath much of the ridge axis (mean depth 1,640 ± 185 m), as are deeper sub‐AML (SAML) reflections (brightest events ~100–800 m below AML). Local sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 102 publications
2
60
0
Order By: Relevance
“…We do not detect a deeper concentrated magma body below the shallow plumbing system, as is observed elsewhere on the EAVS (Pagli et al, ), on Hawaii (e.g., Poland et al, ), and at fast‐spreading MORs (e.g., Marjanović et al, ). Instead, we detect an off‐rift deflating vertically extensive source from ∼1 to 14 km depth, which likely represents a more complex system of smaller stacked sources.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We do not detect a deeper concentrated magma body below the shallow plumbing system, as is observed elsewhere on the EAVS (Pagli et al, ), on Hawaii (e.g., Poland et al, ), and at fast‐spreading MORs (e.g., Marjanović et al, ). Instead, we detect an off‐rift deflating vertically extensive source from ∼1 to 14 km depth, which likely represents a more complex system of smaller stacked sources.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of a potential shallow reservoir overlying a region of axial melt storage at Erta 'Ale and Alu‐Dalafilla on the EAVS (Pagli et al, ) shows similarities to the stacked sill structure observed at spreading ridges with high melt flux, such as the fast‐spreading EPR (e.g., Carbotte et al, ; Marjanović et al, ; Wanless & Behn, ). An important distinction at Erta 'Ale is the largely dike‐fed plumbing system, defined by the local topographic and regional tectonic stress fields (Xu et al, ; Wadge et al, ), rather than a system of stacked sills observed at MORs, although dikes at MORs may simply be difficult to image with reflection seismology (e.g., Marjanović et al, ). Yet the existence of a reservoir at ∼1 km depth at Erta 'Ale and Alu‐Dalafilla indicates that shallow magma bodies may be supported on the EAVS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding about crustal accretion has been changing during the last decade as improved seismic reflection images from different settings provided evidence for more complex crustal magmatic systems. Recent evidence include segmentation of the AML (Carbotte et al, ; Marjanović et al, ), crustal axial melt sills below the AML (Arnulf et al, ; Marjanović et al, ), lower crustal sills in the near axis region (Canales et al, ), and off‐axis magmatic systems (Aghaei et al, ; Canales et al, ; Han et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, high‐resolution studies have improved understanding of fine‐scale, third‐ and fourth‐order ridge segmentation. At fast‐spreading rate segments of the East Pacific Rise (EPR) between 27 and 32°S (Hey et al, ), between 8 and 12°N (e.g., Carbotte et al, ; Soule et al, ; White et al, ), and at 16°N (Le Saout et al, ), and along the intermediate‐spreading rate Galápagos Spreading Center (GSC; Sinton et al, ), studies relating magmatic and hydrothermal processes to deep structure support a strong correlation between morpho‐tectonic segmentation and magmatic lens segmentation (Carbotte et al, , ; Marjanović et al, ; White et al, ). Tomography studies have also shown that tectonic discontinuities are associated with a decrease of mantle melt extraction, and thus, third‐order segmentation of ridges has been attributed to mantle processes (e.g., Toomey et al, ; VanderBeek et al, ).…”
Section: Introductionmentioning
confidence: 99%